Field performances of tractor mounted with various implements: a case study / Nazura Amanda Zainal Abidin - Zainal Abidin, Nazura Amanda (Faculty of Plantation and Agrotechnology, 2019)
Field data performances are important in farm management where the proper used of tractor and implements can minimize inputs and fully optimized the machinery. This study is to investigate the efficiency of the implements. The field performance was evaluated by using Kubota M8540 tractor and various mounted implements in the field. The performance measures effective field capacity, wheel slippage and time taken for the implements to complete individual task. Three implements that used in this study were disc plough, rotary tiller and seed drill at constant engine speed 1500 rpm. All the implements were run on 20 m X 20 m testing site. Time taken was measured in minutes and wheel slippage was calculated in percentage, while field capacity was computed in hectare per hour. The findings of study shows that disc plough has the highest wheel slippage among the implements, meanwhile seed drill has the lowest wheel slippage. Furthermore, rotary tiller took the longest time, followed by then disc plough and seed drill with total time taken of 26.60 min, 23.70 min and 14.52 min respectively. In relation to effective field capacity, seed drill which covered 1.01 hectares per hour was the highest, followed by disc plough of 0.32 hectares per hour and rotary tiller 0.24 hectares per hour. From the performance of implements evaluated, seed drill was the most efficient implement to be used with the tractor. In order to use the machine efficiently, the tractor and implements should be matching properly in size and capacity.